To thine communication partner be true: The effect of presentation consistency on perceived authenticity and liking after making a first impression online - TANG, Nicholas (Institutional Knowledge at Singapore Management University, 2020)
This experiment examines the effects of presentation consistency on perceived authenticity and liking in computer-mediated communication, differentiating between profile views and short online text-based conversations. The experimental design is a 2 (presentation-consistent vs. -inconsistent) × 2 (profile view vs. short conversation) between-subjects experiment using university students (N = 173) in Singapore. Results show higher perceived authenticity (η2p = .29) and liking after short conversations than after profile views without conversations. When there is only a profile view, perceived authenticity is lower when the profile photo is inconsistent with the profile text than when it is consistent (η2p = .05). We discuss these findings in terms of schema tuning, where presentation inconsistencies can be accommodated over time as individuals develop unique mental schemas about their communication partners.